A new genus and four new species of parasitic isopods (Isopoda: Epicaridea) from deep water squat lobster hosts (Decapoda: Anomura) off New Zealand - Williams, Jason D.; Boyko, Christopher B.; Zheng, Justin (Zootaxa, 2026)
Squat lobsters (Decapoda: Anomura) from New Zealand were previously known to be hosts for approximately 25 species of parasitic isopods (Epicaridea). The present study reports on one new genus and four new species of epicaridean isopods collected from galatheoid squat lobster hosts off New Zealand from depths of ~250–1500 m. Three bopyrids (Munidion radagasti sp. nov. on Curtonida endeavourae, Pseudione apoisos sp. nov. on C. isos, and Pseudione bourdoni sp. nov. on Munidopsis victoriae) and one cryptoniscid (Cryptodanalia australis gen. nov., sp. nov. on Phylladiorhynchus australis) are described. Each new species is compared to its morphologically most closely related species, and a table of comparative female morphology for all cryptoniscid genera is provided. Pseudione fibriata Richardson, 1910, is redescribed and a lectotype designated for that species, Pseudione hayi Nierstrasz & Brender à Brandis, 1931, is confirmed from its type host, Grimothea gregaria, and Pseudione sagamiensis Nierstrasz & Brender à Brandis, 1932, is newly reported from New Zealand. These discoveries underscore that the epicaridean fauna of New Zealand is more diverse than previously recognized and that continued examination of decapod hosts is likely to reveal additional undescribed parasites.